The Effect of Rotational Speed of Homogenization on Emulsion Results Obtained Using Soy Lecithin Emulsifier - Namira, Zahra Rahma; Paramita, Vita; Kusumayanti, Heny (Vocational College of Universitas Diponegoro, 2021)
Homogenization is the process of homogenizing particle size in an effort to maintain the stability of a mixture formed from 2 phases that cannot be fused or commonly called emulsions. This study aims to analyze the effect of homogenization speed and differences in solid concentration in homogenization process using homogenizer. The ingredients used are Virgin Coconut Oil as a solute, Aquadest as a solvent, and soy lecithin as an emulsifier. Several stages of analysis are density, viscosity, microscopic, and emulsion stability analysis. The results obtained from this study were optimum stirring speed of 22,000 rpm with optimum homogenization time of 4 minutes, solid concentration of 60% obtaining density of 0.78 gr/mL, viscosity of 5.86 cP, stability of 100%, and most stable microscope test. The results showed that the greater the stirring speed and time, the smaller the density and viscosity value produced and the greater the stability value obtained. The greater the concentration of solids, the greater the density, viscosity, and stability of the emulsion.